2016
DOI: 10.1136/annrheumdis-2015-208476
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated bioenergetics: a key regulator of joint inflammation

Abstract: ObjectivesThis study examines the relationship between synovial hypoxia and cellular bioenergetics with synovial inflammation.MethodsPrimary rheumatoid arthritis synovial fibroblasts (RASF) were cultured with hypoxia, dimethyloxalylglycine (DMOG) or metabolic intermediates. Mitochondrial respiration, mitochondrial DNA mutations, cell invasion, cytokines, glucose and lactate were quantified using specific functional assays. RASF metabolism was assessed by the XF24-Flux Analyzer. Mitochondrial structural morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
213
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(235 citation statements)
references
References 57 publications
22
213
0
Order By: Relevance
“…It has been confirmed that hypoxia presents in the joint microenvironment of RA, and plays a key role in regulating angiogenesis in RA28. Hypoxia alters cellular bioenergetics by inducing mitochondrial dysfunction and promoting a switch to glycolysis, thereby leads to abnormal angiogenesis29. Glycolytic activity is enhanced in the hypoxia microenvironment of synovial tissues in RA30.…”
Section: Discussionmentioning
confidence: 94%
“…It has been confirmed that hypoxia presents in the joint microenvironment of RA, and plays a key role in regulating angiogenesis in RA28. Hypoxia alters cellular bioenergetics by inducing mitochondrial dysfunction and promoting a switch to glycolysis, thereby leads to abnormal angiogenesis29. Glycolytic activity is enhanced in the hypoxia microenvironment of synovial tissues in RA30.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to T cells, synovial RA fibroblasts display an intrinsic ability to employ glycolytic metabolism under metabolic stress. Indeed, glucose deprivation or glycolytic inhibitors impaired their cytokine secretion, proliferation, and migration [63].…”
Section: Metabolic Dysregulation In Ra and Other Autoimmune Conditionsmentioning
confidence: 99%
“…In contrast to T cells, synovial RA fibroblasts display an intrinsic ability to employ glycolytic metabolism under metabolic stress. Indeed, glucose deprivation or glycolytic inhibitors impaired their cytokine secretion, proliferation, and migration [63].Recently a gas chromatography-mass spectrometry study, carried out on sera samples, has highlighted a peculiar metabolic signature of RA patients compared to healthy controls [64]. Specifically, RA patients displayed decreased levels of aas (leucine, phenylalanine, pyroglutamate, serine, isoleucine, methionine, threonine, proline, and valine) and glucose alongside with increased levels of fatty acids such as palmitelaidate, oleate, trans-9-octadecenoate,cis-5,8,11-eicosatrienoate, docosahexaenoate, 2-ketoisocaproateand 3-methyl-2-oxovalerate, and cholesterol.…”
mentioning
confidence: 99%
“…Evidence for this metabolic switch in RA has been demonstrated by several studies showing an increase in mitochondrial dysfunction in the RA synovium [20], along with increased expression of glucose transporters (GLUTs) [21] and glycolytic enzymes, including hexokinase 2 (HK2), pyruvate kinase M2 (PKM2), glyceraldehyde 3-phosphate dehydrogenase (GAPDH), glucose-6-phosphate isomerase (GPI) and LDH [7,8,[21][22][23][24][25]. Marked accumulation of metabolic intermediates including lactate, glutamine, succinate [26] and itaconate [27] have been demonstrated in the RA joint which, in turn, can activate synovial cells Hexokinase 2 (HK2) converts glucose into glucose 6-phosphate dehydrogenase (G6PD).…”
Section: Review Series: Translating Immunometabolismmentioning
confidence: 99%
“…FLS are characterized by increased proliferation, resistance to apoptosis and are potent producers of proinflammatory cytokines and matrix degradation enzymes, resulting in a highly invasive phenotype [71,72]. Previous studies have demonstrated increased mitochondrial dysfunction, coupled by changes in the ultrastructure of mitochondria in RA-FLS in response to inflammatory stimuli, in addition to altered expression of mitochondrial genes associated with apoptosis, redox balance and mitochondrial protein transport [21,23,73]. Metabolic profiling of FLS demonstrated increases in sugar metabolism (glycolysis and PPP) and amino acid metabolism (tyrosine and catecholamine biosynthesis and protein biosynthesis) [74].…”
Section: Role Of Metabolism In Synovial Fibroblast Activation In Ramentioning
confidence: 99%